Supporting the Mental Health and Well-Being of First Responders from Career to Retirement: A Scoping Review. Issue 4 (30th August 2021) - Smith, Erin; Dean, Greg; Holmes, Lisa
Abstract: Introduction: First responders are at greater risk of mental ill health and compromised well-being compared to the general population. It is important to identify strategies that will be effective in supporting mental health, both during and after the first responder's career. Methods: A scoping review was conducted using the PubMed database (1966 to October 1, 2020) and the Google Scholar database (October 1, 2020) using relevant search terms, truncation symbols, and Boolean combination functions. The reference lists of all relevant publications were also reviewed to identify further publications. Results: A total of 172 publications were retrieved by the combined search strategies. Of these, 56 met the inclusion criteria and informed the results of this overview paper. These publications identified that strategies supporting first responder mental health and well-being need to break down stigma and build resilience. Normalizing conversations around mental health is integral for increasing help-seeking behaviors, both during a first responder's career and in retirement. Organizations should consider the implementation of both pre-retirement and post-retirement support strategies to improve mental health and well-being. Conclusion: Strategies for supporting mental health and well-being need to be implemented early in the first responder career and reinforced throughout and into retirement. They should utilize holistic approaches which encourage "reaching in" rather than placing an onus on first responders to "reach out" when they are in crisis.